Humoral immunity to pertussis among mother-baby dyads - O. V. Samodova (Žurnal Infektologii, 2021)
Introduction. Infants younger than 3 months old are at high risk of severe pertussis, complications and pertussis-associated mortality. Newborns receive protection against pertussis from maternal antibodies transferred predominantly during late pregnancy. Neither disease, nor vaccination provides lifelong immunity against pertussis. So most of women have low antibody concentrations, leaving their newborn infant at a higher risk for disease in the first months of life.The aim of this study was to assess the concentration of antibodies against Вordetella pertussis among mother-baby dyads.Methods. We performed a cross-sectional study including 119 mother-baby dyads. Maternal antibodies were measured in venous blood specimens during the last trimester of pregnancy for women and in cord blood for newborn infants.Results. The median age was 30 (25; 34) years. The half of participants had unknown vaccination status (49,6%). Only 12,6% had a protective level (>18 U/mL) of anti-pertussis antibodies, 74,8% of participants had a nonprotective (<14 U/mL) level and 12,6% had an equivocal (14–18 U/mL) antibody concentrations. All newborns of seropositive women and 11,5% infants of women with an equivocal titers receive protection against pertussis. Transplacental transport ratio of antibodies against pertussis was higher in newborns of seropositive women.Conclusion. We revealed a huge proportion of pregnant women (87,4%) and newborns (77,3%) susceptible to pertussis. Maternal antibody level against pertussis was the major predictor of the antibody level in the infant.